1981
DOI: 10.1128/aac.20.1.104
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus prophylaxis for diarrhea due to enterotoxigenic Escherichia coli

Abstract: In vitro and animal experiments indicated that lactobacilli might prevent Escherichia coli from colonizing the intestine and may produce substances counteracting enterotoxin. Lactinex, a commercial preparation of dried Lactobacillus acidophilus and L. bulgaricus, is marketed for uncomplicated diarrhea. Preliminary experiments in nonfasting volunteers indicated that lactobacilli in this preparation colonized the small intestine for up to 6 h. To evaluate the protective efficacy of Lactinex, a double-blind rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

1986
1986
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(33 citation statements)
references
References 19 publications
0
32
0
1
Order By: Relevance
“…In contrast to previous studies using a higher dose, in which the mean incubation periods were typically 25 to 43 h (5,19), the incubation period observed in this study was somewhat longer, generally exceeding 48 h. An extended incubation suggests that the lower-dose inoculum requires more time to colonize the small intestine and reach the high concentrations of bacteria sufficient to cause symptoms. Even though the time to symptom onset was longer in this study, postchallenge ETEC H10407 shedding by naïve subjects was similar in frequency and magnitude to observations in higher-dose challenge studies (3,17,18).…”
Section: Discussionmentioning
confidence: 86%
“…In contrast to previous studies using a higher dose, in which the mean incubation periods were typically 25 to 43 h (5,19), the incubation period observed in this study was somewhat longer, generally exceeding 48 h. An extended incubation suggests that the lower-dose inoculum requires more time to colonize the small intestine and reach the high concentrations of bacteria sufficient to cause symptoms. Even though the time to symptom onset was longer in this study, postchallenge ETEC H10407 shedding by naïve subjects was similar in frequency and magnitude to observations in higher-dose challenge studies (3,17,18).…”
Section: Discussionmentioning
confidence: 86%
“…No signi®cant differences were noted with respect to attack rate, incubation period, duration of diarrhoea, volume or number of liquid stools (Clements et al, 1981), (Table 6 (c)). On the contrary, a prospective double blind investigation of travellers' diarrhoea in 94 tourists travelling to Egypt found that daily intake of 10 10 lactic acid bacteria (L. acidophilus, B. bi®dum, L. bulgaricus, S. thermophilus) signi®cantly reduced the incidence of diarrhoea compared to the placebo treated group (17 cases of diarrhoea in the lactic acid bacteria treated group in comparison with 29 in the placebo treated group, P 0.02) (Black et al, 1989), Table 6 (a).…”
Section: Lactic Acid Bacteria H Hove Et Almentioning
confidence: 95%
“…On the assumption that lactobacilli favorably modify the intestinal flora, the efficacy of the commercial preparation Lactinexwas tested by two groups: Pozo-Olano et al [9], who conducted their trial in travelers to Mexico, and Clements et al [10], who challenged volunteer college students with virulent enterotoxigenic Escherichia coli (ETEC). Recently, Kollaritsch et al [11] distributed a similar dose of Lactobacillus acidophilus to travelers.…”
Section: Lactobacillimentioning
confidence: 99%